Physico-Chemical Analysis of Waste Water from ACC Cement Industry from an Industrial Town – Ghugus (Maharashtra), India - Durge, L. S.; Chilke, A.M.; Chavhan, R. N. (International Journal of Scientific Research in Biological Sciences, 2019)
There are different sources of industrial water pollution, but one of them is the discharge of harmful chemicals and compounds into the water bodies through gutters, due to which the water from the water bodies becomes unsuitable for the drinking and other domestic purposes. Though 72% of the earth surface is covered by the water, only 2.5 to 2.75 percent is fresh water of which 1.75 to 2 % is frozen in glaciers, ice and snow, 0.5 -0.75 % as groundwater and moisture. Thus less than 0.01 % is available to us as a surface water to us from lakes, ponds, rivers, reservoirs and streams only. So it is our prime duty to keep them clean for the survival of not only humans but for all the living beings on this earth planet. Therefor the systematic management of industrial run off is necessary for keeping the balance of an ecosystem. Therefor a pond situated at Nakoda, the water of which is used by the natives for many purposes including drinking is taken for the study of physic-chemical analysis.